The adverbial clauses and their textual-discursive functions in the argumentative answer genre - Calicchio, Fátima Christina (2016)
We aim in this paper to analyze how adverbial hypotaxis can contribute to the construction of argumentativeness of genre argumentative response.  We selected as the object of analysis the textual productions of candidates for the entrance summer exam UEM/2011. Considering   the theoretical panorama,   the functionalism, the hypothesis to be explored in this paper corresponds to the investigation of textual-discursive functions of adverbial clauses that function as guide value, transitional bridge, frame, focus, topical function among other functions in conjunction causes that can contribute to the construction of argumentativeness genre of argumentative response. As a theoretical contribution, we combine studies of functionalist as Mann & Thompson (1988); Matthiessen & Thompson (1988), Theory of Rhetoric Text Structure. According to this theory, the rhetorical relations give coherence to the discourse, giving unity and allowing the producer to achieve its purposes with the text produced, that is, the theory is based on the principle that the text, in addition to the explicit propositions or explicit statements emerge implied propositions characterized as meaning that emerges between two portions of text. Added to this approach: the assumptions Decat (2009), Neves (1997, 2000) and postulations about genre according to the view of Bakhtin (2000).